Morphological Analysis of Derivational Prefixes in Fable Story of “Raja Lebah dan Sesendok Madu” - Lusi Susanti (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2020)
Abstract As we know that language is very important to our life to interaction in our daily life. The purpose of this study to describe the derivation prefixes which happen in the fabled story and will focus an analysis of the derivational prefixes in the fabled story “Raja Lebah dan Sesendok Madu”. This data research is a qualitative description, data collection using the literature study. Data analysis uses word-class classification in the speech section. The results of this study show that Derivational prefixes consist of se-, me-, meN-, ber-, di-. Although they are included in the derivation prefix they also have different in word classes. For example the word “sendok” as a noun and the word “sesendok” as an adverb. Based on the result from the analysis derivational prefixes above we find that there are several words that have different word classes when we add the prefix phonemes in front of a word. For example, the words "sendok" and "sesendok" have different word classes.Keywords: Morphology, Morphemes, derivational prefixes.  AbstrakSeperti yang kita ketahui bahwa bahasa sangat penting bagi kehidupan kita untuk berinteraksi dalam kehidupan sehari-hari. Tujuan dari penelitian ini adalah untuk mendeskripsikan prefiks derivasi yang terjadi pada cerita fabel dan akan memfokuskan analisis prefiks derivasi dalam dongeng “Raja Lebah dan Sesendok Madu”. Data penelitian ini adalah deskriptif kualitatif, pengumpulan data menggunakan studi pustaka. Analisis data menggunakan klasifikasi kelas kata pada bagian pidato. Hasil penelitian ini menunjukkan bahwa prefiks Derivasional terdiri dari se-, me, meN-, ber-, di-. Meskipun mereka termasuk dalam awalan derivasi, mereka juga memiliki kelas kata yang berbeda. Misalnya kata “sendok” sebagai kata benda dan kata “sesendok” sebagai kata keterangan. Berdasarkan hasil analisis prefiks turunan di atas didapatkan bahwa terdapat beberapa kata yang memiliki kelas kata yang berbeda bila kita menambahkan prefiks fonem di depan sebuah kata. Misalnya kata "sendok" dan "sesendok" memiliki kelas kata yang berbeda.Kata kunci: Morfologi, Morfem, prefiks turunan.